2018
DOI: 10.3390/molecules23112738
|View full text |Cite
|
Sign up to set email alerts
|

The Radiostability of Meropenem Trihydrate in Solid State

Abstract: The influence of ionising radiation on the physicochemical properties of meropenem trihydrate in solid state was studied for doses of e-beam radiation: 25 kGy and 400 kGy. In the first part of our studies, we evaluated the possibility of applying radiosterilization to obtain sterile meropenem. No changes for meropenem irradiated with a dose of 25 kGy, the dose required to attain sterility, was confirmed in the results of spectroscopic (FT-IR), thermal (DSC, TGA) and X-ray powder diffraction (XRPD) studies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…The literature data confirms that the most common problem encountered after radiosterilisation of solid drugs is discoloration or yellowing (17)(18). In our study also a colour change of samples after exposure to radiation was reported ñ from white to slight beige.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The literature data confirms that the most common problem encountered after radiosterilisation of solid drugs is discoloration or yellowing (17)(18). In our study also a colour change of samples after exposure to radiation was reported ñ from white to slight beige.…”
Section: Resultssupporting
confidence: 89%
“…Previous research concerning the radiostability of β-lactams antibiotics has confirmed their susceptibility to degradation (12)(13)(14)(15)(16)(17).…”
Section: Resultsmentioning
confidence: 84%
“…Previous research concerning the radiostability of β-lactams antibiotics have confirmed their susceptibility to degradation [7,8,9,10,11,12,13]. Test results—both identification methods and stability tests—carried out for solid ERP reflect this statement.…”
Section: Discussionmentioning
confidence: 62%
“…The literature data confirm that discoloration or yellowing is the most common problem that is encountered after radiosterilisation of solid drugs [11]. What is particularly important, after dissolving the ERP irradiated samples in water for injections, we get clear and colorless solutions.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation